Instructional Teaching Media to Promote Autistic Student’s Learning Engagement - Sari Puspita, L. P. Ayu; Padmadewi, N. N.; Wahyuni, L. G. Eka (Journal of Education Reseach and Evaluation, 2019)
The demand for students with disabilities to get English lesson underlies the use of instructional media to help teachers to convey instructions as well as students in understanding English. Related to this case, this study aims to describe the types of instructional media used by teacher in SLB Negeri 2 Singaraja to teach an autistic student. The research data were gathered through observation, interviews, and document study. Based on the data obtained, it was found that the teacher used four types of instructional media namely videos, pictures, matching exercise, and real objects. As an implication, instructional media used by the teacher can convey instructions to autistic student even though they did not perfectly understand. Autistic student also understood English lesson better through these media than just listening to the teacher’s speech.